Recent Advances in Pediatric Wearable Lower-Limb Exoskeletons for Gait Rehabilitation: A Systematic Review - Josue Pacheco-Cherrez; Juan C. Tudon-Martinez; Jorge de J. Lozoya-Santos (IEEE Access)
Cerebral palsy (CP) is the most common physical disability affecting children, often resulting in reduced quality of life due to challenges with movement control, posture, balance, and increased energy expenditure required to walk. Lower-limb exoskeletons (LLEs) offer a promising alternative to traditional rehabilitation methods, with the potential to improve mobility in children with CP. This review aims to provide an updated overview of mechanical characteristics, control strategies, technological advancements, clinical efficacy, and limitations associated with pediatric LLEs for gait rehabilitation in children with CP. The main objectives were to evaluate the current state of technology, review the clinical outcomes of exoskeleton use, and identify emerging trends and challenges in this field. To achieve this, a comprehensive search was conducted using Scopus and Web of Science databases to identify relevant recent studies published from 2020 onward. A total of 11 studies were included based on pre-defined inclusion and exclusion criteria. The findings suggest that pediatric exoskeletons have shown promise in improving gait parameters, such as walking speed and joint kinematics while reducing the metabolic cost in children with CP. Despite these positive outcomes, challenges remain regarding device customization, long-term adherence, and integration into clinical practice. The review underscores the potential of pediatric exoskeletons to significantly improve mobility and quality of life in children with CP but also emphasizes the need for further research to optimize device design, long-term outcomes, and standardized guidelines and protocols to conduct and evaluate clinical trials. These findings have important implications for clinicians, researchers, and developers who seek to advance the field of pediatric rehabilitation technologies.